MATINYA MESIN PARTAI POLITIK (Studi Kasus Pencalonan Syahri Mulyo dalam Pilkada Kabupaten Tulungagung 2013) - Putri Hergianasari (Cakrawala Jurnal Penelitian Sosial, 2016)
Effective political mobilization in the elections able to overcome various obstacles, so thatthe candidates can campaign more effectively in order to achieve the award. Because ofthe fierce competition, each candidate would increasingly need the right strategy, whichcan better ensure effectiveness and efficiency. This study chose Tulungagung election as atest site, with a couple SAHTO study subjects (Syahri Mulyo-Maryoto Bhirowo). SyahriMulyo is one of eight cadres PDIP candidates in this election, but his appearanceTulungagung seen as an achievement in the history of election battle Tulungagung PDIPwhich is a mass base. This is due to socio-cultural background of the people whomataraman of Tulungagung tend nationalis and abangan.Interestingly, Syahri Mulyo escaped the verification and win despite not being carriedfrom the PDIP is a strong party in Tulungagung and precisely in the stretcher by PKNU.Because private network that is rooted candidates strong one is botoh networking whichare relatives. The networks are not acquired overnight, but has been through a longprocess that is relational relationships with constituents at the time long before thecampaign period.This gives a reference, that the non-party approach can be made effective andappropriate for the area and know the local culture and the role of institutionalapproach was replaced by a weaker party the role of non-electoral party.Keywords: Political Mobilization, Elections, Non Party Approach, Networks